Comprehensive study of ZnO films prepared by filtered cathodic vacuum arc at room temperature - Wang, Y. G. (2014)
Room temperature deposition of high crystal quality zinc oxide (ZnO) films was realized by the filtered cathodic vacuum arc (FCVA) technique. Detrimental macroparticles in the plasma as byproducts of arcing process are removed with an off-plane double bend magnetic filter. The influence of oxygen pressure on the structural, electrical and optical properties of ZnO films were investigated in detail. The crystal structure of ZnO is hexagonal with highly c-axis orientation. Intrinsic stress decreases with an increase of chamber pressure, and near stress-free film was obtained at 1x10-3 Torr. Films with optical transmittance above 90% in the visible range and resistivity as low as 4.1x10-3 Ω cm were prepared at pressure of 5x10-4 Torr. Energetic zinc particles in the cathodic plasma and low substrate temperature enhance the probability of formation of zinc interstitials in the ZnO films. The observation of strong ultraviolet photoluminescence and weak deep level emission at room temperature manifest the high crystal quality of the ZnO films prepared by FCVA. Enlargement of the band gap is observed in the absorption and photoluminescence spectra, the band gap shifts towards lower energy with an increase of oxygen pressure. This phenomenon is attributed to the Burstein–Moss effect.